Blaptica dubia un alimento alternativo sostenible para la producción animal - Alberto José Rincón Atuesta; Nancy Rodríguez Colorado (Mundo Fesc)
Animal feed production has long negatively impacted natural resources, making it necessary to implement alternatives that significantly contribute to sustainable development while also ensuring the nutrition of a growing global population. Insect production has been recognized for its nutritional value, with Blaptica dubia being the most notable. However, there is a lack of information regarding the species' inclusion in animal feed. The following review provides a description of Blaptica dubia's potential as an alternative and sustainable feed for productive animals. The methodology employed was based on information searches supported by the Science Direct and Google Scholar databases. The species' potential and contributions to sustainable production are recognized. It can even replace native feeds in the formulation of diets for species such as soybean meal, soybeans, and corn. It is essential to standardize the substrates for its production.